Characterization of the antagonistic secondary metabolites of Paenibacillus polymyxa MEZ6 against Staphylococcus aureus - Zhao, Na; Huang, Mingjiao; Yang, Yang; Cai, Ruxia; Peng, Jian; Guo, Guo (Frontiers in Microbiology, 2025)
IntroductionPaenibacillus polymyxa is an essential bio-control bacterium capable of producing numerous antagonistic compounds with potential usefulness. Methicillin-resistant Staphylococcus aureus (MRSA) is a significant bacterial strain that infects hospitals and communities, exhibiting considerable antibiotic resistance and posing a substantial threat to human health, thereby becoming a major bio-safety concern worldwide. The purpose of this study was to investigate the antibacterial properties and mechanisms of the secondary metabolites of P. polymyxa (MEZ6) against MRSA.MethodsThis study used microdilution procedures and growth and bactericidal kinetics studies to investigate the effects of MEZ6 metabolites on MRSA, and reverse-phase high-performance liquid chromatography (HPLC) and mass spectrometry (LC/MC) were used to detect the secondary metabolites of MEZ6.Results and discussionThe results show that MEZ6 secondary metabolites can inhibit MRSA growth, prevent biofilm formation, reduce the expression of virulence genes (agrA, spa, and clf-1), disrupt cell structure, increase membrane permeability, and lead to the accumulation of ROS. Through systematic characterization, MEZ6 metabolites maybe tryptophan-associated fraction (TAF). This study establishes a systematic theoretical framework for the development and application of bacterial metabolites.